Ekonomi Politik Ketahanan Pangan di Indonesia: Peran Negara Dalam Menghadapi Krisis Pangan - Viona, Merry; N, Nabila; Katanging, Deva Garcia; Candra, Mellyana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the political economy dynamics of food security in Indonesia and the role of the state in addressing the food crisis. Food security is influenced by complex economic, political, bureaucratic, and socio-economic factors. The state plays a strategic role through subsidy policies, management of food reserves, import regulations, sustainable agricultural development, and food technology innovation. However, policy implementation faces obstacles such as corruption, power imbalances, and complex bureaucracy. Comparative studies with other countries highlight the importance of inclusive and multisectoral approaches. The study recommends bureaucratic reform, improved coordination, and strengthened social protection to achieve sustainable and equitable food security in Indonesia.